Laser-driven rotational dynamics of gas-phase molecules: control and applications - Ren, Xiaoming (Kansas State University, 2013)
In this thesis, our work on developing new techniques to measure and enhance field-free molecular alignment and orientation is described. Non-resonant femtosecond laser pulses are used to align and orient rotationally-cold gas-phase molecules. The time-dependent Schrodinger equation is solved to simulate the experimental results. A single-shot kHz velocity map imaging (VMI) spectrometer is developed for characterizing 1D and 3D alignment. Stimulated by a novel metric for 3D alignment proposed by Makhija et al. [Phys. Rev. A 85,033425 (2012)], a multi-pulse scheme to improve 3D alignment is demonstrated experimentally on difluoro-iodobenzene molecules and the best field-free 3D alignment is achieved. A degenerate four wave mixing probe is developed to overcome limitations in VMI measurement; experiments on different types of molecules show good agreement with computational results. Highly aligned linear molecules are used for high harmonic generation experiments. Due to the high degree of alignment, fractional revivals, variation of revival structure with harmonic order and the shape resonance and Cooper minimum in the photoionization cross section of molecular nitrogen are all observed directly in experiment for the first time. Enhanced orientation from rotationally cold heteronuclear molecules is also demonstrated. We follow the theory developed by Zhang et al. [Phys. Rev. A 83, 043410 (2011)] and demonstrate experimentally for the first time that for rotationally cold carbon monoxide an aligning laser pulse followed by a two-color laser pulse can increase field-free orientation level by almost a factor of three compared to using just the two-color pulse.
Keywords: Molecular alignment; Orientation; High harmonic generation; Physics (0605)